HUKUM DAN ILMU HUKUM DALAM PERSPEKTIF FILSAFAT ILMU - Supriyanta - (Wacana Hukum, 2011)
AbstractThe philosophy of science divides a study into two point of views, those are; positivistic which creates empiric study, and normative which creates normative study. The law study has both of those characteristics; in one hand, it has the real characteristics as a normative study; in the other hand, it has empiric characteristics which, later on, become the object study of sociological jurisprudence and socio legal jurisprudence. Therefore, if it is observed from this point of view, it can be concluded that the normative law study has a particular method of study, while empiric law study can be researched by qualitative or quantitative research methodology towards the characteristics of the data. Keywords: the philosophy of science, sociological  jurisprudence, socio legal jurisprudence